2022
DOI: 10.1093/ejo/cjac038
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of patient-reported outcome measures (PROMs) during surgically-assisted acceleration of orthodontic treatment: a systematic review and meta-analysis

Abstract: Background With the widespread of surgically-assisted orthodontic acceleration, the analysis of patient-reported outcome measures (PROMs) has become very important to assure patient acceptance and satisfaction before adopting any acceleration procedure. Objective This review aimed to critically appraise the available evidence regarding the levels of pain, discomfort, functional impairments, and other patient-reported outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…The orthodontic treatment causes varying degrees of pain and discomfort to the patient, leading to decreased cooperation and may result in treatment discontinuation [ 4 ]. To date, a large number of studies have been conducted on patient-reported outcome measures (PROMs) associated with various orthodontic procedures, such as pain during orthodontic separation [ 5 ], discomfort and functional impairments when using removable and fixed expansion appliances [ 6 ], acceptance of the functional and removable appliances [ 7 , 8 ], oral health-related quality of life (OHRQoL) of patients undergoing clear aligner treatment versus fixed appliances [ 9 ], speech problems and oral functions when using lingual brackets versus labial brackets [ 10 , 11 ], and the acceptability of different retainers at the end of orthodontic treatment [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The orthodontic treatment causes varying degrees of pain and discomfort to the patient, leading to decreased cooperation and may result in treatment discontinuation [ 4 ]. To date, a large number of studies have been conducted on patient-reported outcome measures (PROMs) associated with various orthodontic procedures, such as pain during orthodontic separation [ 5 ], discomfort and functional impairments when using removable and fixed expansion appliances [ 6 ], acceptance of the functional and removable appliances [ 7 , 8 ], oral health-related quality of life (OHRQoL) of patients undergoing clear aligner treatment versus fixed appliances [ 9 ], speech problems and oral functions when using lingual brackets versus labial brackets [ 10 , 11 ], and the acceptability of different retainers at the end of orthodontic treatment [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, several minimally invasive methods have been proposed in the literature, such as corticision, piezocision, microosteo-perforations, and laser-assisted flapless corticotomy [8]. With the widespread usage of surgically assisted orthodontic acceleration, the analysis of patient-reported outcome measures has become very important to ensure patient acceptance and satisfaction before adopting any acceleration procedure [9]. Laser dentistry has become prevalent now.…”
Section: Introductionmentioning
confidence: 99%
“…These procedures are classi ed into two types based on their level of intrusion: conservative (biological, physical, and biomechanical measures) and surgical techniques 7 . Prostaglandins are the most often used biological agents 8 , interleukins 9 , leukotriene 10 , vitamin D 11 platelet rich plasma 12 .Mechanical or physical approach include direct electrical current 13 , pulsed electromagnetic eld 14 , low-energy laser [15][16][17] , and Vibration 18,19 Oral surgical procedures quicken orthodontic treatment by affecting the continuity of the alveolar bone resulting in a decrease in bone density and a corresponding reduction in the bone's resistance to orthodontic tooth movement 20,21 . Surgical approach depends on Regional Acceleratory Phenomenon (RAP) which is a method to speed up orthodontic treatment by accelerating bone remodeling rates and bone density.…”
Section: Introductionmentioning
confidence: 99%